An Empirical UCS Model for Anisotropic Blocky Rock Masses - Huang, Fan; Shen, Jiayi; Cai, Ming; Xu, Chaoshui (Rock mechanics and rock engineering, 2019)
The Hoek–Brown (HB) failure criterion is one of the most widely used failure criteria in rock engineering. Based on the Geological Strength Index (GSI) system, a number of empirical models have been proposed in parallel with this criterion to estimate the strength and deformation properties of rock masses such as uniaxial compressive strength (UCS) and deformation modulus. However, the GSI system does not incorporate the effects of joint orientation β on the quality of a rock mass. This means that these empirical models cannot capture anisotropic rock mass strength caused by joint orientations. In this research, UDEC rock mass models, which are calibrated by laboratory data, are used to investigate the effects of joint orientation on rock mass strength in an unconfined state. The values of UCS obtained from the numerical simulation are then compared with those calculated from traditional empirical UCS models based on the GSI system. The comparison study shows that the value of UCS is significantly overestimated by the traditional empirical model when 10° < β < 45°, which will have serious safety implications for engineering designs. To rectify the problem, based on the analysis of numerical simulation results, an anisotropic weighting factor f β is proposed to be used to refine the empirical UCS model. The modified UCS model is demonstrated to be capable of giving conservative but more accurate prediction of the rock mass strength for various joint orientations, which will result in more optimal and safer engineering designs.